Flexible Working Arrangement, Work-Life Balance dan Kinerja Pekerja Perempuan di Kota Banjarmasin di Tengah Pandemi - Rizky Nastiti; Lisandri Lisandri (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
This study aims to analyze the effect of Flexible Working Arrangement on Work-Life Balance and performance of female workers in Banjarmasin during the pandemic. This research is a quantitative research. The population and sample in this study were 50 female workers who worked in government offices and institutions that had implemented Flexible Working Arrangements during the Covid-19 pandemic. The data was collected by distributing questionnaires both online and in person. Moreover, the data analysis was performed using the regression method. The results of the analysis showed that the Flexible Working Arrangement has an effect on the Work-Life Balance and the performance of female workers in Banjarmasin. This indicates that if Flexible Working Arrangement policy can be implemented properly and provided with supportive working conditions, a balance between work and life as well as a good performance of female workers can be achieved.